An assessment of mathematics self-efficacy of secondary school students in osun state, Nigeria (2011)
The study examined an assessment of mathematics self-efficacy of secondary school students in Osun State. It drawn on 500 students comprising 250 males and 250 females randomly selected from 5 secondary schools in Osogbo. Their ages range between 11-17 years with a mean age of 14 years and a standard deviation of 4. A self - efficacy instrument developed by (Morgan & Jinks 1995) was adapted with mathematics achievement test with r= 0.72 developed by the researcher were used for data collection. Three hypotheses were tested at 0.05 level of significance using student-t test, Pearson Product Moment Correlation and Analysis of Variance (ANOVA) statistical tools. The results indicated that significant difference exists in the mathematics self-efficacy of the subjects based on gender and age groups, and that of mathematics achievement. Based on the findings, it was recommended that Secondary School teachers should always make mathematics class more interesting as this will go a long way to improve the student’s self efficacy and achievements in the subjects.